Contemporary prevalence of pretreatment urinary, sexual, hormonal, and bowel dysfunction: Defining the population at risk for harms of prostate cancer treatment. Issue 8 (7th February 2014) - Resnick, Matthew J.; Barocas, Daniel A.; Morgans, Alicia K.; Phillips, Sharon E.; Chen, Vivien W.; Cooperberg, Matthew R.; Goodman, Michael; Greenfield, Sheldon; Hamilton, Ann S.; Hoffman, Karen E.; Kaplan, Sherri H.; Paddock, Lisa E.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The authors investigated the prevalence of pretreatment urinary, sexual, hormonal, and bowel dysfunction in a contemporary, population‐based prostate cancer cohort. They also explored the associations between baseline function and age, comorbidity, and timing of baseline survey completion with respect to treatment. METHODS The Comparative Effectiveness Analysis of Surgery and Radiation (CEASAR) study is a population‐based, prospective cohort study that enrolled 3691 men with incident prostate cancer during 2011 and 2012. Pretreatment function was ascertained using the Expanded Prostate Cancer Index‐26 (EPIC‐26). Data were stratified by age, comorbidity, and timing of baseline survey completion with respect to treatment. Unadjusted and multivariable linear regression analyses were performed to evaluate the relations between exposures and pretreatment function. RESULTS After applying exclusion criteria, the study cohort comprised 3072 men. A strikingly high proportion of men reported inability to obtain erections satisfactory for intercourse (45%) and some degree of urinary incontinence (17%) at baseline. Sexual function was particularly age‐sensitive, with patients aged ≤60 years reporting summary scores in excess of 30 points higher than patients aged ≥75 years (P < .001). Compared with the healthiest men, highly comorbid patients reported less favorable function in each domain, including urinary incontinence (summary score, 89.5 vs 74.1; P < .001) and sexual function (summary score, 70.8 vs 32.9; P < .001). Although statistically significant differences in summary scores were identified between patients who completed the baseline questionnaire before treatment (52%) versus after treatment (48%), the absolute differences were small (range, 1‐3 points). CONCLUSIONS Patients with newly diagnosed prostate cancer exhibit a wide distribution of pretreatment function. The current data may be used to redefine the population "at risk" for treatment‐related harms. Cancer 2014;120:1263–1271. © 2014 American Cancer Society.